2017
DOI: 10.1017/cem.2017.415
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a primary care paramedic STEMI bypass guideline

Abstract: We found a significant difference in the distribution of stable and unstable patients and fewer patients with indications for an ACI in PCP patients. This PCP STEMI bypass guideline appears feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 16 publications
(21 reference statements)
0
10
0
Order By: Relevance
“…Of note, the study by Kwong et al also found that the most common ACP intervention was a fluid bolus for hypotension, and they found that the median volume infused was only 300 ml. 8 Most importantly, in our population other more serious and advanced interventions were infrequent. While the majority of the clinically important events observed were related to hypotension, these are arguably the patients that would benefit most from urgent PCI and STEMI bypass.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Of note, the study by Kwong et al also found that the most common ACP intervention was a fluid bolus for hypotension, and they found that the median volume infused was only 300 ml. 8 Most importantly, in our population other more serious and advanced interventions were infrequent. While the majority of the clinically important events observed were related to hypotension, these are arguably the patients that would benefit most from urgent PCI and STEMI bypass.…”
Section: Discussionmentioning
confidence: 70%
“…Previous studies have shown an arrest rate of roughly 2% to 3% within similar EMS systems. 5,6,8 PCP paramedics have the skill to rapidly recognize cardiac arrest and deploy an AED and basic airway skills.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kwong et al recently presented data from an urban paramedic service. 5 One year of data included 232 PCP-only STEMI bypass, of which 21/232 (9.1%) had indications for an ACP intervention. Eleven patients experienced cardiac arrest; 10 were successfully resuscitated (5 of these by PCPs).…”
Section: Introductionmentioning
confidence: 99%